Shifting shadows: Assessing the habitat and climate change response of binturong (Arctictis binturong) in the conservation landscape of the Asian continent - Imon Abedin; Tanoy Mukherjee; Ah Ran Kim; Hyun-Woo Kim; Soo Rin Lee; Shantanu Kundu (Ecological Informatics)
Owing to accelerated climate change, recent decades have witnessed a concerning trend of deforestation and habitat conversion, particularly in Asia, leading to significant habitat loss for a large number of wildlife, including several keystones and/or indicator species. The binturong, Arctictis binturong is no exception, facing multiple threats such as habitat loss, hunting pressure, and illegal trade in South and Southeast Asia. Despite these challenges, there is a limited number of comprehensive assessments regarding the ecology of this vulnerable mammal. To address this research gap, the present study aimed to assess the current and future distribution of the binturong across its range and evaluate the potential impacts of climate change on habitat suitability. Out of the 645,903 km2 extant distribution range, only 170,505 km2 (26 %) was found suitable in the present scenario. Further, future climate change projections (SSP245 and SSP585) revealed alarming declines in suitable habitat across all scenarios, with reductions reaching up to 93.78 % under the most severe emission scenario. Within the suitable range, Malaysia exhibited the highest mean habitat suitability score (0.766), while China had the lowest (0.024). Most of the countries sharing the distribution range showed a decrease of habitat suitability in future scenarios by over 10 %, except for Bhutan and China, which showed increases by 30 % to 90 % by 2061–2080 under both SSPs. These projections offer new insights into the potential climate-driven range shift of the binturong from tropical to subtropical regions. Additionally, the evaluation of biological connectivity identified nine transboundary corridors within the distribution range. The corridor between Thailand and Malaysia showed the highest mean connectivity (4.211), while the lowest was observed between Cambodia and Vietnam (0.226). The corridor connectivity is incongruent with habitat suitability in future climate change scenarios, highlighting the necessity for a comprehensive management plan of this indicator species conservation in the wild. In conclusion, this comprehensive SDM assessment of this mammalian species represents the first of its kind, providing crucial ecological information for implementing targeted conservation strategies to ensure the long-term survival in the rapidly changing South and Southeast Asian landscape.